Ischio-Ilial Pinning for Stabilization of Coxofemoral Luxations in Twenty-One Dogs: A Retrospective Evaluation - Beale, B. S.; Lewis, D. D.; Parker, R. B.; Macpherson, G. C.; Kuntz, C. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
Twenty-one dogs with craniodorsal coxofemoral luxation were managed with placement of an ischio-ilial pin. The overall success rate in maintaining reduction was 73%, with pins placed at a central position resulting in the lowest incidence of reluxation (p = 0.095). Postoperative complications included pin migration (n = 2), septic arthritis (n = 1), pressure sores n = 3), and decubital ulcers (n = 1).
Keywords: Coxofemoral luxation